Cognitive Behavioral Therapy for Insomnia (CBT-I) - Aunjitsakul, Warut; Udomratn, Pichet (Journal of the Psychiatric Association of Thailand, 2016)
Insomnia is the most common type of sleep disorders encountered in clinical practice. In the past, the treatment of insomnia involved the prescription of benzodiazepine-receptor agonists along with psycho-education. Nowadays, psychological interventions are increasingly used by applying both the learning and cognitive theories to develop a specific treatment for insomnia, which is called the cognitive behavioral therapy for insomnia (CBT-I). Nowadays CBT-I is recognized as having adequate evidence in terms of efficacy and safety for insomnia. The main characteristic of this treatment is its distinct structure, which consists of many techniques related to both behavior and cognition such as sleep-restriction therapy, stimulus-control therapy, cognitive therapy, sleep hygiene, and relaxation techniques. Furthermore, there are several approaches to CBT-I: self-help CBT-I via the internet, group CBT-I, brief behavioral intervention for insomnia, and CBT with behavioral analysis. Objectives of this review are to firstly aggregate the causes and related theories of insomnia such as the behavioral model, cognitive model and hyperarousal model, and secondly, to determine the treatment approaches of CBT-I. The review has shown that the sleep-restriction therapy is an active ingredient for CBT-I. However, both the stimulus–control therapy and the cognitive therapy also improve the treatment outcome.